Penggunaan Ecobrick dalam Upaya Untuk Mengurangi Volume Limbah Sampah Plastik di Desa Pematang Johar Dusun XV - Dalimunthe, Syaiful; Yasmin, Yasmin; Rembune, Zahwa; Febriani , Nur; Aida , Zuhrina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
According to data from the Ministry of Environment and Forestry (MoEF), Indonesia will produce 19.45 million tons of waste by 2022. Of the total amount of waste, 882.03 thousand tons of it is waste from North Sumatra. This amount of waste makes North Sumatra the seventh largest waste producer in Indonesia. Pematang Johar Village is one of five villages located in Labuhan Deli Sub-district, Deli Serdang Regency. The village consists of 18 hamlets, one of which is hamlet XV Suka Mulia. Hamlet XV is a hamlet that is labeled as an ecobrick hamlet, because hamlet XV is the first hamlet to bring and apply plastic waste processing with the ecobrick method. The application of this ecobrick has been running since five years ago until now. In this research, the method used is a qualitative method supported by literature studies. In addition, this study also used an interview method conducted with the community of Dusun XV Suka Mulia, Pematang Johar Village